Optimization of the immobilization of sweet potato amylase using glutaraldehyde-agarose support. Characterization of the immobilized enzyme - Tavano, Olga Luisa; Fernandez-Lafuente, Roberto; Goulart, Antonio José [UNESP]; Monti, Rubens [UNESP] (Elsevier, 2013)
A simplified procedure for the preparation of immobilized beta-amylase using non-purified extract from fresh sweet potato tubers is established in this paper, using differently activated agarose supports. Beta-amylase glutaraldehyde derivative was the preparation with best features, presenting improved temperature and pH stability and activity. The possibility of reusing the amylase was also shown, when this immobilized enzyme was fully active for five cycles of use. However, immobilization decreased enzyme activity to around 15%. This seems to be mainly due to diffusion limitations of the starch inside the pores of the biocatalyst particles. A fifteen-fold increase in the Km was noticed, while the decrease of Vmax was only 30% (10.1 U mg-1 protein and 7.03 U mg-1 protein for free and immobilized preparations, respectively). © 2013 Elsevier Ltd.
Keywords: Agarose; Beta-amylase; Glutaraldehyde; Immobilization; Sweet potato; Biocatalyst particle; Diffusion limitations; Glutaraldehyde-agarose; Glutaraldehydes; Simplified procedure; Amylases; Proteins; Radioactive waste vitrification; Enzyme immobilization; Ipomoea batatas; Solanum tuberosum